The faces of tragedy a comparative content analysis of the news articles of the Philippine Daily Inquirer and Philippine Star on the coverage of the Ultra (PhilSports Arena) stampede from February 5 to May 31, 2006 - Ke, Bridget Ng 1983-
"This is a comparative content analysis of the news articles of Philippine Daily Inquirer (PDI) and Philippine Star (PS) on the Ultra stampede which happened on February 4, 2006. The news articles belong to the time frame of February 5 to May 31, 2006. The resaercher applied the Agenda-Setting Theory by Donald Shaw and Maxwell McCombs as an aid in determining how PDI and PS represented and reported the tragedy. The theory states that media have the capability to influence how people perceive issues as well as what issues to attend to, based on media's selection, emphasis, treatment, exclusion, and elaboration of them. The news articles were analyzed based on variables of size occupied or total area, section and layout style, presence of graphics, type of news article, focus or subject, attributions and slant of the news articles. Results show that PDI had given more attention to the incident because it published more news articles and graphics. It had also published more news analyses and feature stories, aside from the straight news stories PS, meanwhile, had been more factual on their reporting, with less emphasis on huma side stories, PDI, on the other hand, came out with different angles of human interest. However, PDI has its graphics mostly of victims who are women and children, whose innocence must be protected. With this study, the researcher promotes and suggests journalists to cover tragedy stories with humanity and respect for the victims, as well as to consider the ethical guidelines in handling such situations. The researcher also encourages other researchers to study the state of tragedy reporting in the Philippine journalism and how it can still be improved."